Design, Construction and Performance of Porous and Rubbrised Asphalt Pavement (International Journal of Innovative Research in Computer Science & Technology, 2023)
Moreover, porous asphalts have  volumetric and surface characteristics (e.g., acoustic  absorption, drain ability, texture, and friction). These  characteristics are influenced by both intrinsic (such as  gradation and bitumen content) and extrinsic (such as  traffic load) variables, and the complex phenomena and  processes that give rise to them determine how they  change over time. Deterioration, which consequently  impacts budget, noise, and safety. Despite the  deterioration of so many different and intricate qualities  over time, there aren’t any standards for synergistically  improving the pavement system. So, the goal of this study  is to establish and validate a design methodology that,  when applied to the most important characteristics of  friction courses as a component of a pavement structure,  works in concert. The aforementioned method is based on  extensive literature analyses as well as experiment  conducted in a lab and on-site over a period of time to  assess how the major surface and volumetric qualities  degrade over time.
Keywords: Road engineering; Surface property; Acoustic absorption; Macro texture; Friction; Porous asphalt